Use of DSRC and other sensor signals for vehicular localization - Gong, Yi Lin (2017)
Currently, transit safety is becoming a big concern in people’s daily life. Therefore, an increasing number of applications are coming out. With advancement of technology, vehicular communication network which has a high-accuracy, reliable and real time location identification is coming out, and this is a basis for all the road safety applications. The V2X communication can be performed over Dedicated Short Range Communication (DSRC) technology. In past days, the most common method of localization is using Global Positioning System (GPS). However, the signals of GPS have some environment limitation. Vehicle to anything (V2X) communications is one of the methods which is not only finding the location of vehicle, but also can achieve the information exchange between a vehicle and other elements. This project is focused on receiving the signal from Road Side Unit (RSU) by using a shark fin antenna, low noise amplifier and USRP N210 through GNU radio companion, generating the waveform and determining the Relative Time of Arrival (RTOA) of received signal. After this, analysing the finding RTOA. Insights from this project can help to explore whether this method of vehicle localization using these set of equipment is reliable for real life usage, and find out what improvement can be made in the future work. This project is an important part of the vehicular localization. This report, prepared for the full time Final Year Project, will describe the what the author has done and learnt from the project.